2018
DOI: 10.1177/1756286418802688
|View full text |Cite
|
Sign up to set email alerts
|

Choices for long-term hypertensive control in patients after first-ever hemorrhagic stroke: a nationwide cohort study

Abstract: Background:To compare the long-term clinical outcomes of different antihypertensive drugs in stable patients after acute hemorrhagic stroke (HS).Methods:From January 2001 to December 2013, patients with first-ever primary HS were identified in the National Health Insurance Research Database, Taiwan. Patients with traumatic intracerebral hemorrhage and secondary HS were excluded. Those with first-ever HS were recruited and classified into three groups: (1) angiotensin-converting enzyme inhibitor/angiotensin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that in hemorrhagic stroke survivors, the most effective method to improve prognosis and reduce mortality is preventing recurrent stroke [ 21 ], and blood pressure should be well and intensively controlled to prevent stroke recurrence [ 22 , 23 ]. Although the reduction of blood pressure in the acute phase of hemorrhagic stroke is still controversial, we should still emphasize the importance of long-term treatment of hypertension in patients with previous hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that in hemorrhagic stroke survivors, the most effective method to improve prognosis and reduce mortality is preventing recurrent stroke [ 21 ], and blood pressure should be well and intensively controlled to prevent stroke recurrence [ 22 , 23 ]. Although the reduction of blood pressure in the acute phase of hemorrhagic stroke is still controversial, we should still emphasize the importance of long-term treatment of hypertension in patients with previous hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were non-EH-related factors of hemorrhagic stroke development. The choice for examination of the patients in 6 months and more after the hemorrhagic stroke episode was due to the need for patients to be in a stable phase [14].…”
Section: Methodsmentioning
confidence: 99%
“…An ARB medication possession ratio � 80% was required for the patients in both study groups. Blood sugar and BP levels were not available in the NHIRD, and therefore we adjusted for the types and average numbers of oral antidiabetic drugs (OADs) and antihypertensive medications to mitigate the bias related to different levels of blood sugar and BP [32]. Cohort entry (index date) AU : IchangedCohortentrytoCo was defined as when the patient was diagnosed with T2DM and HTN and prescribed with antihypertensive and antidiabetic medications.…”
Section: Plos Medicinementioning
confidence: 99%